Synthesis, characterization and selective oxidation properties of Ti-containing mesoporous catalysts - Eimer, Griselda Alejandra (2006)
Ti-containing mesoporous catalysts with MCM-41 structure have been successfully prepared by direct hydrothermal synthesis. These mesoporous materials were compared with pure siliceous MCM-41 synthesized at the same conditions. An extended and detailed study, which includes the effects of several factors such as the state and content of Ti, surfactant/Si ratio and template removal technique on the physicochemical properties and catalytic activity of Ti-MCM-41, is presented in this contribution. Various techniques including XRD, FT-IR, DRUV-vis, ICP and N2 adsorption were employed for the materials characterization. An optimum surfactant/Si molar ratio in the synthesis gel for the highest regularity of the formed mesostructure was found. Both the structure stability and the local environment of Ti sites in mesostructures with different degrees of Ti loading (0.10-3.22 wt.%) have been carefully investigated. Based on a combined FT-IR and DRUV-vis study and ICP analysis, it was possible to conclude that Infrared spectroscopy can result a powerful tool to verify the Ti(IV) incorporation into the framework of MCM-41. Therefore, a simple and novel method for estimation of framework Ti content could be developed. Also, these materials were catalytically tested in the oxidation of cyclohexene with aqueous hydrogen peroxide. Finally, the catalysts could be regenerated without any loss in activity/selectivity.